Pengaruh Perbedaan Pelarut Dalam Ekstraksi Herba Seledri (Apium graveolens L.) Terhadap Aktivitas Peredaman Radikal Bebas DPPH - Luluk, Luluk nurjanah; Pratama, Nofran Putra; Sari, Kurnia Rahayu Purnomo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2023)
Background: The decreased physiological function is influenced by age and degenerative diseases. Degenerative diseases can be caused by free radicals. Neutralization of free radicals can be done by giving antioxidants. However, synthetic antioxidants cause many side effects so that natural antioxidants are needed from natural ingredients. Celery (Apium graveolens L.) is a natural antioxidant that can be used as antioxidant because celery contains flavonoid compounds. Objective: This study aims to determine the effect of different solvents of ethanol 96%, ethyl acetate, and n-hexane in the extraction of celery herbs on the free radical scavenging activity of 1,1-diphenyl-2-picrylhydrazyl (DPPH). Method: Celery herbs were extracted using the maceration method to obtain ethanol 96%, ethyl acetate, and n-hexane extracts. The extract was then tested for its free radical scavenging activity using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method using UV-Vis spectrophotometry. The principle of the DPPH method is that a hydrogen atom binds to a free radical, causing the free radical to become a non-radical. Result: The results showed that 96% ethanol extract of celery had the highest antioxidant activity with an IC50 value of 4.084 g/mL, followed by ethyl acetate 15.250 g/mL, and n-hexane 28.206 g/mL. Conclusion: which the three solvents could be categorized as very active.